2023
DOI: 10.1155/2023/3280708
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Anti‐inflammatory Activity of Zinc Oxide Nanoparticles Using Leaf Extract of Senecio chrysanthemoides

Abstract: Nanotechnology has recently appeared as an important study subject in modern material sciences. Greener synthesis of nanoparticles has gained the attention of many scientists because of its integral characteristics such as effectiveness, eco-friendly, and low cost. In the present study by following the green synthesis approach, zinc oxide nanoparticles (ZnO NPs) were formed for the very first time by using Senecio chrysanthemoides leaf extract as a reducing agent. The UV-Vis spectrophotometer was used to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…On the other hand, ZnONPs have shown promise in fighting inflammation. Studies have shown that they can be made in a green way using plant extracts, such as Senecio chrysanthemoides, Euphorbia retusa, and Kalanchoe pinnata [22]. These biosynthesized ZnONPs have been shown to reduce inflammation through mechanisms that involve activating caspase-8 and stopping the production of cytokines that cause inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ZnONPs have shown promise in fighting inflammation. Studies have shown that they can be made in a green way using plant extracts, such as Senecio chrysanthemoides, Euphorbia retusa, and Kalanchoe pinnata [22]. These biosynthesized ZnONPs have been shown to reduce inflammation through mechanisms that involve activating caspase-8 and stopping the production of cytokines that cause inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The EDX spectra displayed the elemental composition, with silver and carbon as predominant elements, suggesting the influence of herbal extracts. In the case of ZnONPs, SEM images revealed distinctive rod-like to short prism shapes, highlighting the versatility of morphology achievable through green synthesis [ 16 ]. The EDX spectra validated the existence of zinc, carbon, and oxygen, in alignment with the synthesis process.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ongoing research is exploring the use of nanomaterials for diagnostic purposes, such as imaging and sensing techniques, further expanding their potential in the field of medicine . Nanotechnology holds promise to treat many chronic diseases, which include cardiovascular, neurological, gastrointestinal, autoimmune inflammatory, infectious, and reproductive diseases, as well as various types of cancer …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ongoing research is exploring the use of nanomaterials for diagnostic purposes, such as imaging and sensing techniques, 7 further expanding their potential in the field of medicine. 8 Nanotechnology holds promise to treat many chronic diseases, which include cardiovascular, 9 neurological, 10 gastrointestinal, 11 autoimmune inflammatory, 12 infectious, 13 and reproductive diseases, 14 as well as various types of cancer. 15 With the help of nanoscience, reproductive assistive technology has revolutionized the field of fertility treatments, and scientists have been able to develop innovative methods that improve the success rates of procedures such as in vitro fertilization (IVF) and sperm selection by utilizing nano-technology.…”
Section: Introductionmentioning
confidence: 99%